English Club Di Sdit Az-Zahra Sragen Dalam Mengembangkan Keterampilan Berbahasa Inggris Tahun Ajaran 2016/2017 - Ekawati, Rendra Ari, Drs. Muhroji, S>e., M.si., M.Pd (2017)
The goals of this research are to describe: 1) the background of English Club in SDIT Az Zahra Sragen. 2) The planning of English Club. 3) The implementation of English Club. 4) The obstacle of the implementation of English Club. 5) The solution of the English Club's problem. 6) The evaluation of English Club in SDIT Az Zahra Sragen. The type of this research is descriptive qualitative in the form of case studies. The informant of this research is the principal, English Club's support, English teachers grade 3, 4, 5, and the students of English Club. The techniques of collecting the data are interview, observation, and documentation. Triangulation is used to check the validity of the data. The data is analyzed through the steps of collecting data, data reduction, data display, and drawing conclusion. The result of this research showed that there is various information about English Club in SDIT Az Zahra Sragen in developing English skill. The results of the data are included: the background of English Club to support students in order to speak English fluently, they can use English well for communication and in preparing English competition. The planning of English Club is included: socialization, idea, funding, the planning before the implementation, and students' preparation. The implementation of English Club is included: material, media, technique, and activity. Speaking is the good one than the other English skill. There are some problems to face, the obstacles are included: when made the material, planning the activities, and the media in developing English skill. The evaluation of English Club is not only focused on English skill, but also evaluation for all aspect in the implementation of English Club.